(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the quality of life using the MENQoL scale in menopausal women in Son Tra district, Da Nang city and to explore some related factors. Subjects and methods: A cross-sectional study was conducted on 509 naturally menopausal women with permanent residence in Son Tra district, Da Nang city from 5/2022-5/2023. Results: The mean score of overall quality of life according to the MENQoL scale was 2.67 ± 0.76. The proportion of menopausal women aged 45-60 with good quality of life was 47.7%. Age, education level, chronic diseases, smoking, regular health check-ups, access to menopausal healthcare information were associated with quality of life with p < 0.05. Conclusions: Comprehensive health screening and counseling programs need to be implemented, with a particular focus on menopausal women aged 45-60 and those with low educational attainment or chronic diseases.